30th Annual Frontiers in Education Conference. Building on a Century of Progress in Engineering Education. Conference Proceedin
DOI: 10.1109/fie.2000.896613
|View full text |Cite
|
Sign up to set email alerts
|

Laboratories teaching concepts in microcontrollers and hardware-software co-design

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The particular importance in the engineering educational context of the practical experience has shown that effective teaching requires an interdependent approach combining theoretical material supported by practical laboratory experiments [16]. Andújar, Mejías and Márquez [17] have developed a augmented remote laboratory (ARL), which offers a training environment that is the same as those in a physical laboratory, proving the possibilities of AR technologies for practical online training in the scientific and engineering fields.…”
Section: Context and Motivation: Educating With Realitymentioning
confidence: 99%
“…The particular importance in the engineering educational context of the practical experience has shown that effective teaching requires an interdependent approach combining theoretical material supported by practical laboratory experiments [16]. Andújar, Mejías and Márquez [17] have developed a augmented remote laboratory (ARL), which offers a training environment that is the same as those in a physical laboratory, proving the possibilities of AR technologies for practical online training in the scientific and engineering fields.…”
Section: Context and Motivation: Educating With Realitymentioning
confidence: 99%
“…Unfortunately, such SBC is not available in the market. We therefore decided to design and develop the SBC as shown in Figures 1 and 2 with the features are as follows: (2), a push button (3), a 4 Â 3 hexadecimal keypad (4), eight LEDs (5), four 7-segment displays (6), and an HD44780 compatible 2 Â 16 alphanumeric LCD (7). The status of the input devices (the DIP switches, push button, and keypad) are read and then sent to the microcontroller through the input ports while data from the microcontroller are sent to the output devices (LEDs and displays) through the output ports.…”
Section: Description Of the Single Board Computer And Associated Softmentioning
confidence: 99%
“…Among of the 8-bit microcontrollers, the MCS-51 family microcontrollers were chosen due to its wide-spread popularity especially as an industry standard, its simple architecture, and the likelihood that they will remain important for years to come [6].…”
Section: Description Of the Single Board Computer And Associated Softmentioning
confidence: 99%
“…It is widely accepted that ongoing innovations in the area of embedded systems in education (Wolf and Madsen, 2000;Beetner et al, 2000) coupled with the potential of TCP/IP networks (Woodroffe et al, 2008;Schreier, 2007) are driving the reassessment of the curriculum in the technical subjects. By themselves, embedded Micro-Electro Mechanical System (MEMS) controllers are increasingly being found in standalone experiments dealing with control, data acquisition and communication with a host computer.…”
Section: Introductionmentioning
confidence: 99%